The complete mitochondrial genome of Buccinum bayani (Gastropoda: Buccininae) in Korea. Issue 6 (3rd June 2022) - Kim, Kang-Rae; Han, Ho-Seop; Kim, Yong Hwi; Park, Jong Yeon; Bang, In-Chul
Abstract: This study is the first to report the complete 15, 262 base pair mitochondrial genome of Buccinum bayani, consisting of 13 protein-coding genes, two ribosomal RNA genes, 22 transfer RNA genes, and a control region (D-loop). The overall base composition of the complete genome is A (29.87%), T (39.11%), G (15.86%), and C (15.16%), with a high AT content of 68.98%. Phylogenetic analysis showed that B. bayani was most closely related to B. undatum . The mitogenome of B. bayani will provide helpful information to further our phylogenetic and evolutionary understanding of the family Buccininae.